Comparative study of diagnostic methods used for monitoring of common grape vine (Vitis vinifera L.) crown gall (Agrobacterium vitis Ophel & Kerr) in Slovenia - Janja LAMOVŠEK; Igor ZIDARIČ; Irena MAVRIČ PLEŠKO; Gregor UREK; Stanislav TRDAN (Acta Agriculturae Slovenica)
Agrobacterium vitis causes common grape vine (Vitis vinifera L.) crown gall disease that destroyed a lot of Slovenian vineyards more than a decade ago. Eighty isolates of Agrobacterium spp. collected during monitoring in 2006 were identified as A. vitis and A. tumefacies by pehA and multiplex PCR method. Tumor-inducing capacity of these strains was assessed on test plants and with PCR methods for detection of the Ti plasmid responsible for tumor induction. With VCF3/VCR3 primer pair six false negatives and no false positives were detected. The high genetic diversity of pathogenic Agrobacterium spp. strains affects the performance of molecular methods, thus biological test should be performed where results from molecular methods are doubtful.